Employee perceptions of diversity management in the hospitality industry - Trishna G. Mistry; Fevzi Okumus; Marissa Orlowski (International Hospitality Review)
Purpose – Diversity management is of great importance in the hospitality industry, resulting in a host of constructive consequences if managed effectively. However, there is a deficiency of investigation surrounding the outcomes of diversity management on the employees' attitudes and behavior in the hospitality industry. This research sought to investigate the influence of diversity management on workers' performance and conduct in the hospitality industry. Design/methodology/approach – This quantitative study used survey data from 565 hospitality industry employees. Structural equation modeling was used to test the relationships from the research model. Findings – This study identified a relationship between diversity management and positive workforce-related outcomes, including job performance, service innovation behavior and employee engagement in the hospitality industry. Research limitations/implications – The findings of this study will push the confines of diversity management scholarship and initiate new paths of academic inquiry. Hospitality industry managers can also identify the benefits of effective diversity management as a consequence of this study. Originality/value – This research contributes to the growing literature on diversity management as an essential aspect of human resources management in promoting positive employee attitudes and behaviors.